Future trends in instrument development in nursing research: From traditional psychometrics to cross-cultural and digital measurement approaches - Chung-Ying Lin; Tram Thi Bich Nguyen (Faculty of Nursing Universitas Padjadjaran, 2026)
Measurement instruments are fundamental to nursing research, as they are a cost-effective method for nursing personnel to quickly understand various health and behaviors, such as quality of life and functional health outcomes. Although many instruments have been developed using traditional psychometric approaches, conventional measurement practices may need to be reevaluated. Specifically, emerging challenges, including cultural diversity in global research, multidimensional health constructs, and the rapid development of digital health technologies, have revealed limitations in conventional measurement practices. This editorial discusses key issues in instrument development within nursing research and highlights future directions for methodological advancement. For example, future effortsshould emphasize rigorous construct validation, cross-cultural adaptation, measurement invariance testing, and the integration of digital and real-time measurement tools. Advancing these approaches will enhance the validity, applicability, and global relevance of measurement instruments, thereby trengthening the evidence base that informs nursing practice, education, and health policy.